ELEVATED BLOOD PRESSURE AMONG ADULTS AGED ABOVE 18 YEARS OBTAINING CARE AT A SELECTED TEACHING HOSPITAL IN KIGALI CITY - Jean De Dieu Ishimwe, Jocelyne Uwambajimana, Dr. Ogendi Japheths (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background Non-communicable diseases (NCDs) are an expanding global public health problem, especially in developed countries. Elevated blood pressure is a public health problem that is a major cause of morbidity .The study was aimed to determine prevalence and factor associate with elevated blood pressure among adults aged above 18 years obtaining care at Kibagabaga hospital in Kigali city. Methods The study was cross-sectional study. Consecutive sampling technique was used for selecting study participants. The sample size was 286 adults aged above 18 years obtaining care at Kibagabaga hospital in Kigali city. A structured questionnaire, blood pressure measurement and anthropometric measurement and were used to collect data. SPSS Version 21 was used for data analysis. Descriptive analysis, chi square, and multivariable logistic regression analysis were used. At 95% confidence level, P < 0.05 was considered statistically significant Results A total of 286 adults above 18 years obtaining care at Kibagabaga hospital in Kigali city have been interviewed. The age range is 21 years old and 92 years old, with an age mean of 55.43 and a standard deviation of 13.917. The prevalence of elevated blood pressure was 17.5%. Factors associated with elevated blood pressure among adults aged above 18 years were alcohol consumption that is correlated with a higher risk of developing elevated blood pressure. where Respondents who consume alcohol were found to have approximately 7.8 times higher odds of having elevated blood pressure and they were significantly associated (AOR=7.848; 95%CI: 1.164-52.919; p=0.034) compared to those who do not consume alcohol. There was a correlation found between diabetes and elevated blood pressure. Respondents with diabetes were more likely to experience elevated blood pressure (AOR=3.094, 95%CI: 1.134-8.437, P=0.027) compared to those who had not diabetes. Family history of hypertension was significantly associated with 2.7 times great chance to develop elevated blood pressure in individuals who had family history of hypertension (AOR = 2.751, 95% CI: 1.254-6.035, p=0.012) compared to those who had not. Conclusion This study showed that prevalence of elevated blood is high therefore there was a need to guide policymakers, health professionals, researchers, and stakeholders to prioritize areas and interventions. There should be routine examination of blood pressure among patients. This will enable early detection, control, and treatment after availing of protocol, policy, and guidelines